Methanogens at the top of the world: occurrence and potential activity of methanogens in newly deglaciated soils in high-altitude cold deserts in the Western Himalayas - Aschenbach, Katrin; Conrad, Ralf; Řeháková, Klára; Doležal, Jiří; Janatková, Kateřina; Angel, Roey (Frontiers in Microbiology, 2013)
Methanogens typically occur in reduced anoxic environments. However, in recent studies it has been shown that many aerated upland soils, including desert soils also host active methanogens. Here we show that soil samples from high–altitude cold deserts in the western Himalayas (Ladakh, India) produce CH4 after incubation as slurry under anoxic conditions at rates comparable to those of hot desert soils. Samples of matured soil from three different vegetation belts (arid, steppe, and subnival) were compared with younger soils originating from frontal and lateral moraines of receding glaciers. While methanogenic rates were higher in the samples from matured soils, CH4 was also produced in the samples from the recently deglaciated moraines. In both young and matured soils, those covered by a biological soil crust (biocrust) were more active than their bare counterparts. Isotopic analysis showed that in both cases CH4 was initially produced from H2/CO2 but later mostly from acetate. Analysis of the archaeal community in the in situ soil samples revealed a clear dominance of sequences related to Thaumarchaeota, while the methanogenic community comprised only a minor fraction of the archaeal community. Similar to other aerated soils, the methanogenic community was comprised almost solely of the genera Methanosarcina and Methanocella, and possibly also Methanobacterium in some cases. Nevertheless, approximately 103 gdw-1 soil methanogens were already present in the young moraine soil together with cyanobacteria. Our results demonstrate that Methanosarcina and Methanocella not only tolerate atmospheric oxygen but are also able to survive in these harsh cold environments. Their occurrence in newly deglaciated soils shows that they are early colonisers of desert soils, similar to cyanobacteria, and may play a role in the development of desert biocrusts.